Pengembangan Kurikulum Pendidikan Agama Islam 2013 Integratif dalam Menghadapi Era Society 5.0 - Khoirin, Dalila; Hamami, Tasman (State Islamic Institute of Madura, 2021)
This study aims to develop the 2013 PAI curriculum through the integration of all curriculum components with the abilities needed in the era of society 5.0. The potentials required at the period of society 5.0 are the ability to solve problems, think critically and creatively, which will help humans to be able to take advantage of innovations in the industrial era 4.0. These abilities will be more optimal if accompanied by good manners. Therefore the 2013 PAI curriculum has a principal role in making it happen. Qualitative approaches and types of literature research are using in this study. Hence the data sources are taken from library sources. Research data were collected using documentation techniques, then analyzed by reading, understanding, examining, connecting, and concluding. From this research, it can be seen that the integration of society 5.0 era capabilities into the 2013 PAI curriculum will help educators to form a generation of nations who are ready to compete in the era of society 5.0 by mastering good character-based science and technology.Penelitian ini bertujuan mengembangkan kurikulum PAI 2013 melalui integrasi semua komponen kurikulum dengan kemampuan yang dibutuhkan di era society 5.0. Kemampuan yang dibutuhkan di era society 5.0 adalah kemampuan dalam menyelesaikan masalah, berpikir kritis dan kreatif, yang akan membantu manusia untuk bisa memanfaatkan inovasi yang ada di era industry 4.0. Kemampuan-kemampuan tersebut akan lebih optimal jika disertai dengan budi pekerti yang baik, oleh karena itu kurikulum PAI 2013 memiliki peran penting dalam mewujudkannya. Pendekatan kualitatif dan jenis penelitian kepustakaan yang digunakan dalam penelitian ini, oleh karena itu, sumber data diambil dari sumber pustaka. Data-data penelitian dikumpulkan dengan teknik dokumentasi, kemudian dianalisis dengan membaca, memahami, memeriksa, menghubungkan dan menyimpulkannya. Dari penelitian ini dapat diketahui bahwa pengintegrasian kemampuan era society 5.0 ke dalam kurikulum PAI 2013 akan membantu pendidik untuk membentuk generasi bangsa yang siap bersaing di era masyarakat 5.0 dengan menguasai ilmu pengetahuan dan teknologi berbasis budi pekerti yang baik.